The influence of comorbid disorders on the episodicity of bipolar disorder in youth. (17th October 2015) - Yen, S.; Stout, R.; Hower, H.; Killam, M. A.; Weinstock, L. M.; Topor, D. R.; Dickstein, D. P.; Hunt, J. I.; Gill, M. K.; Goldstein, T. R.; Goldstein, B. I.; Ryan, N. D.; et al.
Abstract : Objective: Bipolar disorder (BP) frequently co‐occurs with other psychiatric disorders. We examine whether course of anxiety disorders (ANX), attention deficit hyperactivity disorder (ADHD), disruptive behavior disorders (DBD), and substance use disorders (SUD) influence likelihood of recovery and recurrence of depression and mania in BP youth. Method: Weekly ratings of psychiatric disorder intensity were obtained from 413 participants of the Course and Outcome of BP Youth project, followed for an average of 7.75 years. Multiple‐event Cox proportional hazards regression analyses examined worsening of comorbid disorders as predictors of mood episode recovery and recurrence. Results: Increased severity in ANX and SUD predicted longer time to recovery and less time to next depressive episode, and less time to next manic episode. Multivariate models with ANX and SUD found that significant effects of ANX remained, but SUD only predicted longer time to depression recovery. Increased severity of ADHD and DBD predicted shorter time to recurrence for depressive and manic episodes. Conclusion: There are significant time‐varying relationships between the course of comorbid disorders and episodicity of depression and mania in BP youth. Worsening of comorbid conditions may present as a precursor to mood episode recurrence or warn of mood episode protraction.